1998
DOI: 10.1332/030557398782025691
|View full text |Cite
|
Sign up to set email alerts
|

Employment Equity Policies in Canada and the Netherlands: enhancing minority employment between public controversy and market initiative

Abstract: English Time and again employment statistics document the marginal position of (ethnic) minority groups within the labour force in Western multicultural nation states. There seems to be a broad, if differently motivated, consensus among politicians, employers and pressure groups that this situation cannot be prolonged with impunity. However, where it comes down to indicating the underlying causes and defining adequate solutions and policies, shared concern quickly dissolves into controversy. Legal measures to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In some states, ethnic monitoring evokes memories of racial categorisation during the Second World War. 75 In others, it is contrary to rules on data protection and even explicitly forbidden as an element of anti-discrimination law. 76 At a practical level, the utility of the data in part depends on the existence of broader population statistics permitting firms to know the relative proportions of different ethnic groups.…”
Section: Monitoring and Data Collectionmentioning
confidence: 99%
“…In some states, ethnic monitoring evokes memories of racial categorisation during the Second World War. 75 In others, it is contrary to rules on data protection and even explicitly forbidden as an element of anti-discrimination law. 76 At a practical level, the utility of the data in part depends on the existence of broader population statistics permitting firms to know the relative proportions of different ethnic groups.…”
Section: Monitoring and Data Collectionmentioning
confidence: 99%
“…Starting in the 1980s various action programs and legislation were developed in order to stimulate employment equity both in the spheres of corporate business and public administration. Gradually, mandatory regulations were abolished and exchanged for voluntary amendments and the practice of diversity management (Glastra et al, 1998). Until the policy statement of the new minority government consisting of liberal-conservatives and Christian-democrats with populist support in October 2010 explicitly made an end to them, employment policies for public administration stressed diversity and equal opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst Stephanopolous and Edley's (1995) review of the effectiveness of affirmative action in the USA found that overall, the extent to which affirmative action had expanded minority employment in skilled positions was unclear, the programmes considered were effective, but could possibly be implemented in a fairer manner. Evaluation of the effectiveness of affirmative action statutory laws and policy instruments in the Netherlands has been seen largely as a 'bureaucratic monstrosity' (Glastra et al, 1998) due to the added burden it places on employers.…”
mentioning
confidence: 99%